Odpowiedzi

2010-03-02T15:27:37+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10
b) 2x-2=7-x
2x+x=7+2
3x=9
c) 10=4-2x
-2x=-10+4
-2x=-6
d) -(2x-1)=4
-2x+1=4
-2x=3
e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-t=7
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
2010-03-02T15:34:30+01:00
A) -3x-2x=-10
-5x=-10 /-5
x=2
b) 2x+x=7+2
3x=9 /3
x=3
c) 2x=4-10
2x=-6 /2
x=-3
d) -2x+1=4
-2x=4-1
-2x=3 /-2
x= -1,5
e)2x+2=x
2x-x =-2
x=-2
f) 2t-3t-1=6
-t =6+1
-t=7 /-1
t=7
g) -4-x=6-2x
-x+2x=6+4
x=10
h) 3y+18-y=2y+18
3y-y-2y=18-18
0=0